THE SUPPLEMENTARY FEEDING EFFECT IN BALI CATTLE TO CALF LENGTH DIMENSION - Nugraha, Harry Yoga; Sampura, Putu; Suatha, I Ketut (Buletin Veteriner Udayana; Vol. 8 No. 2 Agustus 2016, 2016)
The research was carried out to determine the effect of supplementary feeding in bali cattle to length dimensions of the calf. The research object used 16 bali cattle and newborn calf of bali cattle. eight calf of bali cattle from the cow who is given additional food and eight calf of bali cattle for the cow is not given additional food are maintained by farmers in Sobangan village, Mengwi district, Badung regency. The research was conducted by means of supplementary feeding in the cow after six months of pregnancy (during the three months before birth). The data analyzed by T test. The result showed that the size of the long dimension of calf with supplement feeding compared with feeding control not significant.
Keywords: sapi bali, dimensi panjang, pengaruh pemberian pakan, bali cattle, the long dimension, the effect of feeding